Parameter Kinetik Char Hasil Pirolisis Serbuk Kayu Mahoni (Switenia Macrophylla) dengan Variasi Heating Rate dan 1 Temperatur - Majedi, Farid; Wijayanti, Widya; Hamidi, Nurkholis (Rekayasa Mesin, 2015)
The value of k (rate constant) is one of the important parameters in the equation speed of reaction (kinetics of reactions). This paper discusses the value of k (rate constan) at each heating rate (673 K / h and 873 K / h). Where k is the value obtained by calculating the value of k temperature 523 K, 623 K, 723 K, 773 K and 873 K heating rate of 673 K / h and k values of temperature 523 K, 623 K, 723 K, 773 K and 873 K heating rate 1073 K / h. From the k value of each temperature, calculated values of k in the heating rate. Calculation results obtained kinetic parameters heating rate of 673 K / h Kinetic is ð‘˜ = 24,022 . ð‘’ âˆ’1230 ð‘‡ â„ , Ea = 10226.2 kJ Mol -1 , A = 269.4548 min -1 and a heating rate of 1073 K / h is ð‘˜ = 8,998 . ð‘’ , Ea = 6550.6 kJ Mol -1 , A = 100.9273 min . From the k value of each heating rate validated into the mass loss is calculated, which obtain the actual mass loss results with the mass loss calculation results of kinetic equations for each temperature and heating rate can be seen that the value of mass loss value calculation results is approaching mass reduction so the actual kinetic equation respectively temperature and heating rate. Rate constan) is one of the important parameters in the equation speed of reaction (kinetics of reactions) -1